Conjunctival Chemosis and Annular Ciliochoroidal Detachments Detected by Anterior-Segment Optical Coherence Tomography in a Case of Systemic Lupus Erythematosus - Akiko Ishida; Yukari Yamane; Yasurou Koyama; Manabu Honda; Masahiro Kondo; Yohko Murakawa; Masaki Tanito (Case Reports in Ophthalmology, 2021)
A 61-year-old Japanese woman presented to our hospital for treatment of systemic serositis associated with systemic lupus erythematosus (SLE). At the initial ophthalmologic examination, her best-corrected visual acuity was 1.2 and 0.6 in her right and left eyes, respectively. Slit-lamp examination showed marked chemosis in both eyes (OU). Swept source-based, anterior-segment optical coherence tomography (AS-OCT) clearly showed conjunctival elevations corresponding to the chemosis in all scan directions OU. In some scans, hyporeflective spaces with luminal structures corresponding to dilated lymphatic channels and nonluminal structures corresponding to interstitial fluid accumulation were seen clearly under the conjunctival epithelium and/or in the parenchyma. In all scan directions, the supraciliary space was seen clearly, suggesting the presence of an annular ciliochoroidal detachment. Fundus examinations showed retinal edema temporal to the optic nerve head and subfoveal serous retinal detachments OU. Ocular effusions resolved by 2 weeks after the start of steroid pulse therapy, and pleural effusions and ascites resolved and pericardial effusion decreased by 2 months. AS-OCT can be useful for understanding the mechanism(s) of the less common anterior-segment ocular manifestations of SLE.